The Effect of Financial Literacy, Financial Inclusion, and QRIS-Based Digital Payments on the Performance of Small and Medium Enterprises (SMEs) in Lowokwaru District - Stepanie Margareta; Hermi Sularsih; Poppy Indrihastuti (International Journal of Management and Business, 2026)
This study aims to analyze the effect of financial literacy, financial inclusion, and digital payment (QRIS) on the performance of Small and Medium Enterprises (SMEs) in Lowokwaru District, Malang City. This study employs a quantitative approach with an explanatory research design and multiple linear regression analysis. The population consisted of 3,424 food and beverage SMEs, with a sample of 97 respondents determined using the Slovin formula and purposive sampling technique. Data were collected through a 1-5 Likert scale questionnaire and analyzed using SPSS 25. The results show that financial literacy has a positive and significant effect on SME performance (Sig. 0.007), financial inclusion has a positive and significant effect and is the most dominant variable (Sig. 0.000), and QRIS digital payment has a positive and significant effect on SME performance (Sig. 0.000). The coefficient of determination (R²) of 0.347 indicates that the three independent variables explain 34.7% of the variation in SME performance, while the remaining 65.3% is influenced by other factors outside the model. This study recommends improving financial literacy, expanding access to formal financial services, and optimizing the use of QRIS to support the growth and sustainability of SMEs.